Upper Gastrointestinal Crohn’s Disease: Literature Review and Case Presentation - Soorya N. Aggarwal; Yana Cavanagh; Lan Wang; Amer Akmal; Matthew A. Grossman (Case Reports in Gastrointestinal Medicine)
Upper gastrointestinal tract predominant Crohn’s Disease (CD) remains an elusive clinical entity, manifesting limited or vague symptomatology, eluding clinical suspicion, and delaying subsequent diagnostic evaluation. As a result, it has not been widely described and there is a lack of clear recommendations for diagnosis or management. Standard IBD evaluation including serologic testing, imaging, and endoscopy may initially not be fruitful. Furthermore, endoscopic evaluation may be grossly normal in patients without long standing-disease. We describe an 18-year-old male who presented with only unexplained, persistent iron-deficiency anemia. Extensive outpatient testing including multiple endoscopic evaluations with standard biopsies was unfruitful. Ultimately, a positive fecal calprotectin prompted enteroscopy with endoscopic mucosal resection (EMR) in an effort to obtain a larger, deeper tissue specimen. Grossly cobblestoned mucosa along with histopathology revealing focal crypt abscesses, chronic inflammation in the lamina propria, and superficial foveolar epithelial regenerative changes were consistent with CD. This patient’s case illustrates the need for a high degree of suspicion for CD in patients with unexplained or persistent iron deficiency anemias. Persistent investigation yielded an elevation in fecal calprotectin suggesting underlying gastrointestinal inflammation and prompted advanced endoscopic evaluation with EMR. Waxing and waning tissue findings are characteristic of CD and pose a unique challenge in patients with upper gastrointestinal predominant pathology. As such, diligent workup including laboratory evaluation, imaging, and serial endoscopy is critical to establish pathology and dictate subsequent management in IBD, especially upper gastrointestinal tract predominant CD.